Ministry of Health 6th annual national health research conference : invest now and start reaping your health rewards - Ministry of Health
This research conference was held on November 26-27,2015, at the Jamaica Conference Centre under the theme "Invest Now and Start Reaping your Health Rewards". The programme for the two days of activities were included along with other useful information on the event or relating to the event.
Keywords: Programmes. -- Jamaica